Exercise prevents fatty liver by modifying the compensatory response of mitochondrial metabolism to excess substrate availability - Miriam Hoene; Lisa Kappler; Laxmikanth Kollipara; Chunxiu Hu; Martin Irmler; Daniel Bleher; Christoph Hoffmann; Johannes Beckers; Martin Hrabě de Angelis; Hans-Ulrich Häring; Andreas L. Birkenfeld; Andreas Peter; et al. (Elsevier, 2021)
Objective: Liver mitochondria adapt to high-calorie intake. We investigated how exercise alters the early compensatory response of mitochondria, thus preventing fatty liver disease as a long-term consequence of overnutrition. Methods: We compared the effects of a steatogenic high-energy diet (HED) for six weeks on mitochondrial metabolism of sedentary and treadmill-trained C57BL/6N mice. We applied multi-OMICs analyses to study the alterations in the proteome, transcriptome, and lipids in isolated mitochondria of liver and skeletal muscle as well as in whole tissue and examined the functional consequences by high-resolution respirometry. Results: HED increased the respiratory capacity of isolated liver mitochondria, both in sedentary and in trained mice. However, proteomics analysis of the mitochondria and transcriptomics indicated that training modified the adaptation of the hepatic metabolism to HED on the level of respiratory complex I, glucose oxidation, pyruvate and acetyl-CoA metabolism, and lipogenesis. Training also counteracted the HED-induced glucose intolerance, the increase in fasting insulin, and in liver fat by lowering diacylglycerol species and c-Jun N-terminal kinase (JNK) phosphorylation in the livers of trained HED-fed mice, two mechanisms that can reverse hepatic insulin resistance. In skeletal muscle, the combination of HED and training improved the oxidative capacity to a greater extent than training alone by increasing respiration of isolated mitochondria and total mitochondrial protein content. Conclusion: We provide a comprehensive insight into the early adaptations of mitochondria in the liver and skeletal muscle to HED and endurance training. Our results suggest that exercise disconnects the HED-induced increase in mitochondrial substrate oxidation from pyruvate and acetyl-CoA-driven lipid synthesis. This could contribute to the prevention of deleterious long-term effects of high fat and sugar intake on hepatic mitochondrial function and insulin sensitivity.